2022
DOI: 10.1101/2022.06.08.495145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the Diverse Effects of Divisive Normalization on Noise Correlations

Abstract: Divisive normalization, a prominent model of interactions between neurons, plays a key role in influential theories of neural coding. Testing the mechanistic basis of those theories requires understanding the relationship between normalization and the statistics of neural activity, particularly noise correlations which provide strong constrains on circuit models. Yet the relation between normalization and correlations remains unclear, because models of covariability typically ignore normalization despite emp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 148 publications
(378 reference statements)
0
1
0
Order By: Relevance
“…For example, several important recent studies have begun to explore how recurrent circuit mechanisms might implement dynamic fluctuations in neural activity ( Heeger and Mackey, 2019 ; Heeger and Zemlianova, 2020 ) and have postulated that shifts in the balanced excitation and inhibition that is thought to underlie normalized average responses when two stimuli are presented might contribute to sizeable positive or negative spike count correlations ( Verhoef and Maunsell, 2017 ). Finally, recent work by Coen-Cagli and colleagues proposes a method of assessing normalization strength on individual trials and demonstrated a connection between the neural responses that are well-described under a normalization model and the level of variability of firing that they show ( Coen-Cagli and Solomon, 2019 ; Weiss et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several important recent studies have begun to explore how recurrent circuit mechanisms might implement dynamic fluctuations in neural activity ( Heeger and Mackey, 2019 ; Heeger and Zemlianova, 2020 ) and have postulated that shifts in the balanced excitation and inhibition that is thought to underlie normalized average responses when two stimuli are presented might contribute to sizeable positive or negative spike count correlations ( Verhoef and Maunsell, 2017 ). Finally, recent work by Coen-Cagli and colleagues proposes a method of assessing normalization strength on individual trials and demonstrated a connection between the neural responses that are well-described under a normalization model and the level of variability of firing that they show ( Coen-Cagli and Solomon, 2019 ; Weiss et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A natural and important extension of this work is to additionally consider pairwise and population-level response statistics (such as pairwise noise correlations and the geometry of population activity). These statistics have been studied extensively in cortical areas [177][178][179] , are influenced by similar factors as those that elicit response sub-additivity and variability quenching 38,51,[180][181][182][183][184] and further constrain models of neural activity. Response sub-additivity and variability quenching co-occur under various experimental manipulations.…”
Section: [H1]conclusionmentioning
confidence: 99%
“…Note that we primarily discuss data collected in cat and monkey. Recent work in rodent V1 has revealed similar sub-additive phenomena (and is rapidly advancing our understanding of the underlying circuit mechanisms [42][43][44][45][46][47][48] ), but studies of response variability in rodent V1 have thus far been less extensive than in these other species (but see [49][50][51] ).…”
Section: [H1] Introductionmentioning
confidence: 99%